The pragmatic aspect of the translation of phraseological units in advertising texts. - Shukhratova Mukhlisakhon Shukhratjon qizi (Genius Journals, 2022)
This study is devoted to the study of the features of the use of phraseological units in the light of the pragmatic assignment of the advertising text. The relevance of this study is related to the existing areas of development of the theory and practice of translating texts of a special pragmatic orientation, providing communication in the field of mass communication, which include advertising texts. The ability of a text to produce a pragmatic effect on the addressee is called the pragmatic aspect. If the pragmatic aspect is conveyed in translation, the text is considered pragmatically adequate, while lexical accuracy contributes to the preservation of pragmatics
Keywords: Metaphor; Phenomenon; Metalanguage Of Linguistics